2017
DOI: 10.1128/aac.02374-16
|View full text |Cite
|
Sign up to set email alerts
|

A Case-Control Study of Molecular Epidemiology in Relation to Azithromycin Resistance in Neisseria gonorrhoeae Isolates Collected in Amsterdam, the Netherlands, between 2008 and 2015

Abstract: resistance to ceftriaxone and azithromycin is increasing, which threatens the recommended dual therapy. We used molecular epidemiology to identify clusters and associations with azithromycin resistance in Amsterdam, the Netherlands. isolates ( = 143) were selected from patients visiting the Amsterdam STI Outpatient Clinic from January 2008 through September 2015. We included all 69 azithromycin-resistant isolates (MIC ≥ 2.0 mg/liter) and 74 frequency-matched susceptible controls (MIC ≤ 0.25 mg/liter). The meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 41 publications
1
11
1
Order By: Relevance
“…However, many studies, including our present study, showed N. gonorrhoeae strains with an AZM MIC of 1 g/ml carried the C2611T mutated 23S rRNA allele or mtrR gene (5,(11)(12)(13). It is noteworthy that AZM resistance determinants were also recognized in N. gonorrhoeae isolates with AZM MICs of Ͻ1 g/ml (11,12,14). Close monitoring and further research is needed to monitor the evolution of wild-type N. gonorrhoeae.…”
Section: Discussionmentioning
confidence: 51%
“…However, many studies, including our present study, showed N. gonorrhoeae strains with an AZM MIC of 1 g/ml carried the C2611T mutated 23S rRNA allele or mtrR gene (5,(11)(12)(13). It is noteworthy that AZM resistance determinants were also recognized in N. gonorrhoeae isolates with AZM MICs of Ͻ1 g/ml (11,12,14). Close monitoring and further research is needed to monitor the evolution of wild-type N. gonorrhoeae.…”
Section: Discussionmentioning
confidence: 51%
“…We observed high variability in both alleles and ST in our study population, which could be due to sampling over a prolonged time period and from different risk groups (MSM and women reporting anal sex or symptoms). For example, ST2212, ST2992, ST5441 and ST5793 are more prevalent in MSM than heterosexual men or women [10,22,23]. In our study, these STs were mainly found in MSM, but eight samples with ST2992 and one with ST5793 were from women.…”
Section: Discussionmentioning
confidence: 47%
“…DNA sequence analysis revealed that all 14 isolates harbored the mosaic-mtr and the A2059G mutation in all four copies of their 23S rRNA gene. While investigators from many countries have reported on the A2059G mutation or the mosaic-mtr, none described these two haplotypes together (5,10,(12)(13)(14)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). The 14 isolates in this study are the first known isolates to have possessed both the A2059G mutation and the mosaic-mtr.…”
Section: Resultsmentioning
confidence: 79%
“…In the United States, the percentage of isolates with reduced cephalosporin susceptibility declined after 2012; however, the number and percentage of gonococcal isolates with reduced susceptibility to azithromycin have steadily increased since then (11). The increase in the number of N. gonorrhoeae isolates displaying elevated MICs to azithromycin is typically associated with the accumulation of genetic mutations in the multiple transferable resistance (mtr) locus or in the 23S rRNA gene (10,(12)(13)(14).…”
mentioning
confidence: 99%